Repairing Interfacial Defects in Self‐Assembled Monolayers for High‐Efficiency Perovskite Solar Cells and Organic Photovoltaics through the SAM@Pseudo‐Planar Monolayer Strategy - Hung, Chieh‐Ming; Wu, Chi‐Chi; Yang, Yu‐Hsuan; Chen, Bo‐Han; Lu, Chih‐Hsuan; Chu, Che‐Chun; Cheng, Chun‐Hao; Yang, Chun‐Yun; Lin, Yan‐Ding; Cheng, Ching‐Hsuan; Chen, Jiann‐Yeu; Ni, I‐Chih; et al. (Advanced science, 2024)
Lately, carbazole‐based self‐assembled monolayers (SAMs) are widely employed as effective hole‐selective layers (HSLs) in inverted perovskite solar cells (PSCs). Nevertheless, these SAMs tend to aggregate in solvents due to their amphiphilic nature, hindering the formation of a monolayer on the ITO substrate and impeding effective passivation of deep defects in the perovskites. In this study, a series of new SAMs including DPA‐B‐PY, CBZ‐B‐PY, POZ‐B‐PY, POZ‐PY, POZ‐T‐PY, and POZ‐BT‐PY are synthesized, which are employed as interfacial repairers and coated atop CNph SAM to form a robust CNph SAM@pseudo‐planar monolayer as HSL in efficient inverted PSCs. The CNph SAM@pseudo‐planar monolayer strategy enables a well‐aligned interface with perovskites, synergistically promoting perovskite crystal growth, improving charge extraction/transport, and minimizing nonradiative interfacial recombination loss. As a result, the POZ‐BT‐PY‐modified PSC realizes an impressively enhanced solar efficiency of up to 24.45% together with a fill factor of 82.63%. Furthermore, a wide bandgap PSC achieving over 19% efficiency. Upon treatment with the CNph SAM@pseudo‐planar monolayer, also demonstrates a non‐fullerene organic photovoltaics (OPVs) based on the PM6:BTP‐eC9 blend, which achieves an efficiency of 17.07%. Importantly, these modified PSCs and OPVs all show remarkably improved stability under various testing conditions compared to their control counterparts.